Changes in Diacetyl and Amino Acid Concentration during the Fermentation of Dry-Hopped Beer: A Look at Twelve Saccharomyces Species and Strains. (3rd April 2023) - Bruner, James; Marcus, Andrew; Fox, Glen
Abstract: Hops were traditionally used in brewing for the addition of isomerized alpha acids that balance the sugary wort with bitterness, though modern breweries are dry-hopping to add complex and unique aromas to their beers. An unintended consequence of high amounts of dry-hopping is the phenomenon known as hop creep, causing an increase in alcohol, carbonation, and diacetyl concentrations. The amount of diacetyl in a beer can be directly correlated to yeast health and vitality, controlled by the amount of free amino nitrogen (FAN) available to the yeast. In this study, both diacetyl and amino acid concentrations were measured prior to and 24 h after dry-hopping, at terminal gravity, and at the start of fermentation. These values were compared across twelve yeasts that are commonly used in dry-hopped beer or offer unique characteristics to fermentation. Experimental yeasts BY881, WLP518, K-97, and CK S102 all exhibited diacetyl concentrations below the aroma threshold for beer. The addition of dry-hops added a significant ( p < 0.05) increase in FAN content to the fermenting beers, with most of the increases in serine, arginine, glutamate/glutamine, alanine, and glycine. These increases did not parallel the amino acid content measured in the grist or hops, where asparagine/aspartic acid, proline, and glutamate/glutamine were most prominent. Correlations between total FAN content and diacetyl concentration were calculated, as diacetyl is a precursor in the biosynthesis pathway of the amino acids valine and leucine. However, in this experiment, no correlation of amino acid and diacetyl concentration was observed between dry-hopped and traditional fermentations.